The Role of Competence, Motivation and Training in Increasing Employee Commitment in Insurance Companies - Wildatul Aluf Rahmadani; Nurul Qomariah; Abadi Sanosra; Nursaid Nursaid (Budapest International Research and Critics University, 2023)
The insurance company is one of the non-bank companies that also contribute to increasing economic activity in Indonesia. The increasing number of insurance companies in Indonesia has also increased competition in the insurance sector. This study aims to examine the effect of employee competence, work motivation and training on employee commitment at PT Asuransi Ramayana Tbk Jember. The independent variable consists of competency variable (X1), motivational variable (X2) and job training variable (X3) while the dependent variable is employee commitment (Y). A total of 125 employees of PT. Ramayana Insurance Tbk. Jember (which includes 3 working areas namely Jember Regency, Banyuwangi Regency and Probolinggo Regency) which is the population as well as the sample or respondent. Test the reliability and validity of the data as a test measuring tool in this study. Hypothesis test to test the hypothesis in this study. The results of the study show that employee competence has an impact on employee commitment. The variable of work motivation has an impact on employee commitment and training has a significant effect on employee commitment.